Spolni stereotipi in sodobni slovenski roman - Zupan Sosič, Alojzija (Primerjalna književnost, 2007)
In the modern Slovenian novel (1990-2007), sexual stereotyping is realized in the sense of postmodernist esthetics, which establishes a humorous, ironic, and grotesque distance toward stereotypes. Among the stereotypes discussed (the dark continent, the house angel, the femme fatale, the femme fragile, the guardian of the house, and Don Juan), the stereotype of the dark continent, which represents a traditional experience of the woman as a mystery, is the most frequent.
Keywords: Slovene literature; slovenska književnost; slovenski roman; spolne vloge; stereotipi